Abdullah, Adel al-Sheikh. “Arabic Sciences and the Methodology of Combining the Two Readings,” Year 7, Issue 28 (Spring 1423 AH/ 2002 CE), Pp. 95-122. - عبد الله عادل الشيخ (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2002)
Adel al-Sheikh Abdullah’s article discusses the concept of combining the two readings (reading of the universe and the reading of revelation), and questions whether the Arabic sciences are in need of a process of Islamization. It reviews the justifications for the renewal of Arabic linguistic thought, attempting to establish it (intellectually and methodologically) upon referral to principal Islamic sources (i.e., ta’ṣīl). It then explains methodological renewal, which it considers the core of the contemporary intellectual problem, and epistemological renewal, and questions whether linguistic knowledge among Arabs have contributed anything. It identifies the major issues of the Islamic-oriented linguistics science, such as the relationship between the Arabic language and Islamic sciences, and issues of translation and localization (Arabization). It concludes with explaining the extent to which we are in need of a contemporary methodology for the future that benefits from the elements of contemporary linguistics and is guided by the purposes of Islam (maqāṣid) and Islam's higher values, such as tawḥīd (monotheism), tazkiyyah (purification), and ʿumrān (civilizational development or social and economic development).